Estudio de pre-factibilidad para la instalación de una planta productora de envases herméticos de polipropileno - Meave Gaviria, Javier Bernardo (2016)
This Project is based in the installation of a Production plant of an air polypropylene tight containers in the city of Lima. The objective is to investigate and determinate the viability of the market, economy, finance and technical of this Project. In the market study was done a survey to 50 people who were well received this product in the national market. The main center of distribution will be supermarkets such as Wong, Plaza Vea, Tottus, Metro y Vivanda, evaluating the posibility of expanding in the future.